2010
DOI: 10.1111/j.1600-0633.2009.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between water temperatures and upstream migration, cold water refuge use, and spawning of adult bull trout from the Lostine River, Oregon, USA

Abstract: Understanding thermal habitat use by migratory fish has been limited by difficulties in matching fish locations with water temperatures. To describe spatial and temporal patterns of thermal habitat use by migratory adult bull trout, Salvelinus confluentus, that spawn in the Lostine River, Oregon, we employed a combination of archival temperature tags, radio tags, and thermographs. We also compared temperatures of the tagged fish to ambient water temperatures to determine if the fish were using thermal refuges.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Furthermore, it can also be influenced by behavioural cues and life history; developmental and migratory stage may have different thermal tolerances. Although ideal bull trout survival and reproduction temperature is less than 15 o C, Hillman and Essig () and Howell et al () have shown that they can adapt their life cycle to a wide range of temperature thresholds. The Environmental Protection Agency recommends a temperature range between 12 and 14 o C, which differs from the 4 to 10 o C optimal temperature for juvenile bull trout growth and rearing habitat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it can also be influenced by behavioural cues and life history; developmental and migratory stage may have different thermal tolerances. Although ideal bull trout survival and reproduction temperature is less than 15 o C, Hillman and Essig () and Howell et al () have shown that they can adapt their life cycle to a wide range of temperature thresholds. The Environmental Protection Agency recommends a temperature range between 12 and 14 o C, which differs from the 4 to 10 o C optimal temperature for juvenile bull trout growth and rearing habitat.…”
Section: Methodsmentioning
confidence: 99%
“…Bull trout is a cold water obligate species and sensitive to temperature change (Fraley & Shepard, 1989;Rieman & Mclntyre, 1993); thermal requirements may vary with geographic area and life-history expression (Anglin et al, 2004;Hillman & Essig, 1998;Howell, Dunham, & Sankovich, 2010;Poole et al, 2001;Selong, McMahon, Zale, & Barrows, 2001). Furthermore, it can also be influenced by behavioural cues and life history; developmental and migratory stage may have different thermal tolerances.…”
Section: Preference Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the system, thermal refuge may be available in the form of a tributary, varying water depth, outflow of a hydroelectric dam, discharge from a power plant cooling operation, hyporheic flow or groundwater discharge from a spring (Nielsen et al 1994;Peterson & Rabeni 1996;Torgersen et al 1999;Cooke et al 2004;Young & Isely 2007). Much of our current knowledge about thermal refuge use by fishes is based on salmonids (Torgersen et al 1999;Ebersole et al 2001;Howell et al 2010), but many other species of fish use thermal refuge (Peterson & Rabeni 1996;Labbe & Fausch 2000). Juvenile Coho salmon (Oncorhynchus kisutch) that thermoregulate in streams grew faster by moving between cold habitats with abundant food and warmer habitats that provided metabolic and assimilative benefits (Armstrong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At a coarse spatial scale, groundwater can influence the distribution and abundance of aquatic organisms [23], [24] and reduce the occurrence of temperature fluctuations that may result in reproductive failure of certain species [25]. At fine spatial scales, some fishes show behavioral responses to thermal refuges by selecting spawning locations [26], [27], avoiding ice break up and frazil ice [28], or thermoregulating by occupying groundwater influenced areas during warm or cool water periods [16], [19], [20], [29].…”
Section: Introductionmentioning
confidence: 99%